2017
DOI: 10.15376/biores.12.3.4958-4971
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-lignin and Xylan-lignin Interactions on the Formation of Lignin-derived Phenols in Pyrolysis Oil

Abstract: To gain a better understanding of the effect of the interactions between two biomass components (cellulose-lignin and xylan-lignin) on ligninderived phenolic products, two analysis methods are introduced. With 3:1, 2:1, and 1:1 ratios of cellulose and lignin, and xylan and lignin, the mixtures were subjected to fast pyrolysis, which was carried out in a fixed-bed tubular furnace at 450 to 600 °C. The phenolic content in the bio-oils was analyzed by gas chromatography-mass spectrometry. The product distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The main factors affecting the final product and its distribution of thermal cracking are biomass material properties (type and particle size), pyrolysis reaction temperature, heating rate, gas phase residence time, catalyst, and reaction pressure, etc. (Liu et al 2017;Dong et al 2018). There are varieties of biomass pyrolysis processes, but the essence of their chemical reaction is the free radical mechanism (Demirbaş 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The main factors affecting the final product and its distribution of thermal cracking are biomass material properties (type and particle size), pyrolysis reaction temperature, heating rate, gas phase residence time, catalyst, and reaction pressure, etc. (Liu et al 2017;Dong et al 2018). There are varieties of biomass pyrolysis processes, but the essence of their chemical reaction is the free radical mechanism (Demirbaş 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This overlap in regime 2 (313–438 °C) could lead to CH–π interactions between cellulose and lignin, enhancing lignin-derived products such as phenolics. 35,36 These observations highlight that in the pyrolytic ‘melt-phase’, interactions between the biopolymers indeed exist but in a narrow temperature range with the overlapping of cellulose and lignin decomposition. Therefore, this paper is focused on the influences of lignin on cellulose decomposition.…”
Section: Introductionmentioning
confidence: 87%
“…al. [38] studied the pyrolysis of a mixture of cellulose and lignin. They showed that the increase in bio-oil yield with increasing cellulose content was not proven, indicating that lignin inhibited cellulose pyrolysis to bio-oil.…”
Section: ) Biomass Type and Compositionmentioning
confidence: 99%